Irrigation Energy Sources and Profit Efficiency of Vegetable Farming in the Keta Municipality, Volta Region (Ghana Journal of Science, Technology and Development, 2021)
This study estimated and compared profit and profit efficiency levels of energy sources for irrigation in the Keta Municipality of Ghana. The data was analysed using profit and Stochastic Frontier Analyses. The multi-stage sampling technique was used to sample 250 respondents. A semi-structured questionnaire was used via face-to-face interview to collect data from the respondents. The most profitable energy source for irrigated vegetable production is solar energy while the least profitable is petrol energy. On average, farmers had a profit efficiency of 59%. The study concluded that energy sources have significant effects on the profit levels of vegetable production as well as the profit efficiency level of the farmer. Solar-powered irrigation facilities should be promoted in the study area and Ghana as a whole.